Hubungan Pengungkapan Diri dan Stres Remaja Penyintas Gempa Bumi Kota Palu - Fadlunnida, Fadlunnida; Karmiyati, Diah; Hidayati, Diana Savitri (Cognicia, 2019)
The earthquake that took place in Palu certainly caused psychological injuries to the survivors, especially teenager. They were required to accepted the situation in an instant. However, if the demands cannot be fulfilled, they will be in a stressful situation. Self disclosure can be used to deal with stress. Feelings of relief  and emotional support will help teens to overcome the problems. This study aimed to investigate the correlation between self disclosure and stress among teenager who survived the earthquake in Palu. The instrument that researcher used were a scale compiled by Khoyroh (2016) and Bunda (201) that had been modified. The subjects were 129 respondents. This study used correlational design with purposive sampling. Subjects were teenagers between the age of 12-21 who survived from the earthquake happened in Palu. The instrument used were Data were analysed using the Pearson Product Moment. Correlation results showed that there was negative correlation between self disclosure and stress among teenagers. Coefficient value of the correlation (r) was -0,246 with p = 0,005 (< 0,0)1. It can be conclude,  the higher the teenagers disclose themselves, the lower risk of stress they will perceived.  The contribution of the self disclosure to the stress was 6,1%.